Jednostka paremiczna w europejskich i amerykańskich nurtach lingwistycznych - Szutkowski, Tomasz (Studia Rossica Posnaniensia, 2015)
This article contains a review of modern paremiological trends, especially in French, Czech, Finnish, Estonian and American science centers. The author presents a synthesis of recent research studies with regard to different aspects of and problems associated with this issue.